2009
DOI: 10.3171/2009.01.focus08309
|View full text |Cite
|
Sign up to set email alerts
|

Optimal surgical treatment for moyamoya disease in adults: direct versus indirect bypass

Abstract: Moyamoya disease is a chronic cerebrovascular occlusive disorder that results in severe morbidity and death. There is much controversy surrounding the optimal treatment for adult patients with the disorder. There have been no randomized trials to assess the efficacy of any single surgical treatment, and existing case series suffer from inadequate power, selection bias, and inherent differences in patient characteristics. In this article the authors review the literature concerning the optimal surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 44 publications
0
35
0
2
Order By: Relevance
“…Blood-vessel anastomosis has been successfully used to develop collateral circulation after myocardial infarction and in patients with Moyamoya disease [21] . Molecular bypass using VEGF preparations has also been used to promote the development of collateral circulation after myocardial infarction and in patients with peripheral vascular ischemic diseases [2][3][4] .…”
Section: Discussionmentioning
confidence: 99%
“…Blood-vessel anastomosis has been successfully used to develop collateral circulation after myocardial infarction and in patients with Moyamoya disease [21] . Molecular bypass using VEGF preparations has also been used to promote the development of collateral circulation after myocardial infarction and in patients with peripheral vascular ischemic diseases [2][3][4] .…”
Section: Discussionmentioning
confidence: 99%
“…STA-MCA bypass surgery has a high rate of patency and has been associated with good clinical outcomes, particularly in drastically improving CBF and thus diminishing the incidence of recurrent ischemic events [8,14,15,16]. Surgical approaches are divided into 3 groups: direct anastomosis, indirect anastomosis and combined anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…2,5,7,23,31 Starke et al reviewed the literature concerning the surgical treatment and concluded that both direct and indirect bypass were effective. 30 Since there is a lack of randomized trials, it was noted that the selection of the surgical modalities depended on the preference and surgical technique mastered by the cerebrovascular neurosurgeon. 17 Furthermore, it is well known that patients with DM tend to develop stroke events in cerebrovascular and cardiovascular diseases.…”
Section: Surgical Treatmentmentioning
confidence: 99%